Essays on subjective Well-Being - Zeydanli, Tugba (2017)
This dissertation consists of three essays on subjective well-being. The first essay examines whether aggregate job satisfaction in a certain labor market environment can have an impact on individual-level job satisfaction. We seek an answer to this question using two different datasets from the United Kingdom characterizing two diferent labor market environments: Workplace Employment Relations Survey (WERS) at the workplace level (i.e., narrowly defined worker groups) and British Household Panel Survey (BHPS) at the local labor market level (i.e., larger worker groups defined in industry X region cells). Implementing an original empirical strategy to identify spillover effects, we find that one standard deviation increase in aggregate job satisfaction leads to a 0.42 standard deviation increase in individual-level job satisfaction at the workplace level and 0.15 standard deviation increase in individual-level job satisfaction at the local labor market level. These social interactions effects are sizable and should not be ignored in assessing the effectiveness of the policies designed to improve job satisfaction. Individuals tend to self-report higher subjective well-being levels on certain days of the weeks than they do on the remaining days, controlling for observed variation. The second essay tests whether this empirical observation suffers from selection bias by using the 2008 release of the British Household Panel Survey. In other words, we examine if subjective well-being is correlated with unobserved characteristics that lead the individuals to take the interview on specific days of the week. We focus on two distinct well-being measures: job satisfaction and happiness. We provide convincing evidence for both of these measures that the interviews are not randomly distributed across the days of the week. In other words, individuals with certain unobserved characteristics tend to take the interviews selectively. We conclude that a considerable part of the day-of-the-week patterns can be explained by a standard "non-random sorting on unobservables" argument rather than "mood fluctuations". This means that the day-of-the-week estimates reported in the literature are likely to be biased and should be treated cautiously. In Sub-Saharan Africa, some scholars identify ethnicity as a cause of instability and poor economic growth, which is due to worse public policies. Eifert, Miguel, and Posner (2010) show that ethnic identification is more prominent during competitive election periods in comparison to other identifying categories such as gender, religion, and class/occupation. The third essay utilizes data from 12 Sub-Saharan African countries and over 40,000 respondents taken from the Afrobarometer. It asks if individual subjective well-being changes in the run up to competitive elections. We find strong evidence that individual subjective well-being does change. It is positively related to the proximity to an election and this proximity effect depends on the competitiveness of the election. We further investigate the background mechanisms behind this positive relationship i.e.: to what extent does well-being of the individual change if the party that the individual supports wins the election, and is there a change in well-being of the individual before and after the election? In addition, we document that ethnic identification also has a positive impact on individual well-being after controlling for electoral cycle variables. Policy makers should internalize these positive externalities driven from politically-induced ethnic identification.